2011
DOI: 10.4236/nm.2011.22016
|View full text |Cite
|
Sign up to set email alerts
|

Re-Parameterization the Logistic Model in Assessing Changes in the Baroreceptor Reflex

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The use of a threshold and saturation and a second order system was essential for the implementation of the model as a relaxation oscillator. Thresholds and saturation have been a cornerstone of models of the baroreflex, which is a fundamental feedback circuit controlling BP (Chen and Kuo-Chu, 1991 ; Ottesen, 2000 ; Chen and Shi, 2011 ; Ottesen and Olufsen, 2011 ; Mahdi et al, 2013 ). Adding stochastic variations to the threshold in the feedback loop not only simulated the low frequency variations in systolic levels referred to as Mayer waves (Cheng et al, 2004 ; Julien, 2006 ), but also demonstrated that the model naturally implemented the Baroreceptor Sensitivity, which has been an important feature when describing cardiovascular regulation (Davos et al, 2002 ; La Rovere et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…The use of a threshold and saturation and a second order system was essential for the implementation of the model as a relaxation oscillator. Thresholds and saturation have been a cornerstone of models of the baroreflex, which is a fundamental feedback circuit controlling BP (Chen and Kuo-Chu, 1991 ; Ottesen, 2000 ; Chen and Shi, 2011 ; Ottesen and Olufsen, 2011 ; Mahdi et al, 2013 ). Adding stochastic variations to the threshold in the feedback loop not only simulated the low frequency variations in systolic levels referred to as Mayer waves (Cheng et al, 2004 ; Julien, 2006 ), but also demonstrated that the model naturally implemented the Baroreceptor Sensitivity, which has been an important feature when describing cardiovascular regulation (Davos et al, 2002 ; La Rovere et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…The non-linear element ( f 1 , Figure 1 ), was modeled as piecewise linear with threshold, T , and saturation, S . This nonlinear feedback is responsible for making the system oscillate, mimics the non-linear feedback present in the baroreflex ( 28 , 29 ) and is a minimal structure for inducing relaxation oscillations ( 25 ). The realization of these integrators by central circuits is not known, but may be accomplished through functional commissural connections between neurons in the rostral ventrolateral medulla (RVLM) and those in the nucleus tractus solitarius NTS) ( 30 , 31 ).…”
Section: Resultsmentioning
confidence: 99%
“…The model was implemented as a state determined second order relaxation oscillator, whose oscillation characteristics are governed essentially by a threshold and saturation mechanism in the feedback loop and a driving signal that maintains the oscillations. The threshold non-linearity, which has been observed in the baroreflex feedback ( 28 , 29 , 49 ), puts the system into systolic or diastolic mode. The model was adapted from work done on modeling oculomotor oscillations during nystagmus ( 25 ) and repetitive motion of the legs during locomotion ( 50 , 51 ) where there are also oscillating fast and slow components of the stepping.…”
Section: Discussionmentioning
confidence: 99%
“…the maximal gain) and standard error were calculated as described previously. 37 The significance of the difference in the maximal gains of the active versus sedentary groups was determined using the z -statistics.…”
Section: Methodsmentioning
confidence: 99%